A numerical solution for dispersal of air pollutants (MAUSAM, 1980)
The dispersal of pollutants from an elevated point source was computed by a numerical method. The computations were made with forward time differences. But backward space differences were used for computing the horizontal advecion of polluants. As eddy diffusivity, which varied with altitude (Z), was used in the numerical computations. The results were compared with a Gaussian plume, and it was observed that the latter did not provide correct estimates at larger distances downstream, because it neglected the horizontal advection of pollutants. The paper presents a comparison between a numerical solution of the diffusion equation, and a Gaussian plume model, for different atmospheric conditions.